2016
DOI: 10.2196/jmir.5994
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Exchange and Discovery in the Age of Social Media: The Journey From Inception to Establishment of a Parent-Led Web-Based Research Advisory Community for Childhood Disability

Abstract: BackgroundEfforts to involve parents and families in all aspects of research, from initiating the question through to dissemination and knowledge exchange, are increasing. While social media as a method for health communication has shown numerous benefits, including increasing accessibility, interactions with others, and access to health care information, little work has been published on the use of social media to enhance research partnerships.ObjectiveOur objective was to describe the development and evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 21 publications
1
45
0
2
Order By: Relevance
“…The CanChild Centre for Childhood Research evaluated the success of a private Facebook group designed to connect parents of children with disabilities with researchers. They reported that parents appreciated the sense of community from the group but Bwanted more researcher participationî n the group (Russell, et al, 2016) clinical trials relevant to rare disease communities are often accessible only through research, and researcher participation might allow patients and their families to remain up to date about interventions or treatment opportunities or advance understanding of disease for the entire medical community. Including researchers and/or clinicians as members of a rare disease group might be seen as an additional opportunity to access to information, medical advice, or research that otherwise might not have been available.…”
Section: Discussionmentioning
confidence: 99%
“…The CanChild Centre for Childhood Research evaluated the success of a private Facebook group designed to connect parents of children with disabilities with researchers. They reported that parents appreciated the sense of community from the group but Bwanted more researcher participationî n the group (Russell, et al, 2016) clinical trials relevant to rare disease communities are often accessible only through research, and researcher participation might allow patients and their families to remain up to date about interventions or treatment opportunities or advance understanding of disease for the entire medical community. Including researchers and/or clinicians as members of a rare disease group might be seen as an additional opportunity to access to information, medical advice, or research that otherwise might not have been available.…”
Section: Discussionmentioning
confidence: 99%
“…Types of publications were varied; we included primary research articles (4/18, 21%), conference proceedings (4/18, 21%), primary research abstracts (2/18, 11%), reports (2/18, 11%), discussion papers (2/18, 11%), an editorial (1/18, 5%), a review (1/18, 5%), a scientific poster (1/18, 5%), and a quality improvement paper (1/18, 5%). The aims of publications were also varied: 7 discussed the benefits and implications of using social media for communicating science to the public [21-26]; 3 studies aimed to develop, test, and disseminate lay summaries of evidence [27-29]; 2 publications aimed to discuss various prospects, priorities, and strategies for improving SC with the public [4,10]; 1 publication summarized articles regarding prospects for SC in the Web 2.0. era [30]; 1 publication presented international SC experiences [31]; 1 publication aimed to provide guidance on how to identify the public’s information needs and conduct deliberative SC [32]; 1 publication advocated for adopting a community-partnered participatory research approach to SC [33]; 1 publication aimed to develop and evaluate a Web-based research advisory community [34]; and 1 publication aimed to explore the concept of science literacy in relation to SC [35]. We also identified the type of SC described in each publication according to the classification of Palmer and Schibeci [17].…”
Section: Resultsmentioning
confidence: 99%
“…The iCAN and other platforms that serve to highlight the voices of children and youth in paediatric medicine has increased over the last decade [ 8 , 14 , 15 ]. Patient-oriented research initiatives such as the Canadian Institutes of Health Research Strategy for Patient-Oriented Research (CIHR SPOR) [ 16 ] have contributed in part to the increased involvement of this demographic [ 17 ].…”
Section: Discussionmentioning
confidence: 99%